The Role of Classical Islamic Educational Institutions before the Emeregence of Madrasah - Abbas, Ngatmin; Rochmawan, Alfian Eko; Astoko, Dudi Budi (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The purpose of this research is to investigate the role of Islamic educational institutions before the emergence of madrasahs in the intellectual and social development of Muslims. The main issue addressed is the contribution of institutions such as al-dars, ribaths, mosques, kuttabs, and scholars' houses in shaping Islamic intellectuality during that time. This study employs a qualitative approach through historical and social analysis. The findings of the research indicate that these institutions were crucial in shaping Islamic intellectuality. They not only served as places to study religious teachings but also helped disseminate knowledge, share ideas, and build the social identity of Muslims. These institutions supported the exchange of ideas, research, and the teaching of knowledge, which were essential for the education of Muslim generations. In conclusion, this research emphasizes the importance of classical Islamic educational institutions in shaping Islamic civilization. These institutions fostered a holistic educational approach that integrated knowledge, religion, and spirituality. They reflect various forms of Islamic education, allowing for comprehensive and integrated learning and continuous knowledge enhancement. The legacy of Islamic educational institutions before madrasahs historically continues to influence how we understand and approach Islamic education today.